Do training, career development, and motivation affect employee performance? - Purwana, Dedi; Hamdi, Yusuf Nur; Yohana, Corry; Effendi, Mohammad Sofwan; Feriady, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
There are some of programs given by the company that expected would improve employee performance which is training and career development. This research aims to analyze the impact of training and career development on employee performance with motivation as a mediator at An Indonesian Shipping Company. This research used a quantitative approach. Data were collected by distributing questionnaires to 114 respondents. SEM (Structural Equation Modeling) was utilized for data analysis. The study confirmed that career development and motivation had a significant influence on employee performance, whereas training did not affect employee performance. It was also found that motivation was able to be a mediator effect of career development toward employee performance. Meanwhile, motivation was failed to mediate training toward employee performance. Recommendations for future studies are discussed.